2021
DOI: 10.3389/fphar.2020.621538
|View full text |Cite
|
Sign up to set email alerts
|

Carveol a Naturally-Derived Potent and Emerging Nrf2 Activator Protects Against Acetaminophen-Induced Hepatotoxicity

Abstract: Acetaminophen (N-acetyl p-aminophenol or APAP) is used worldwide for its antipyretic and anti-inflammatory potential. However, APAP overdose sometimes causes severe liver damage. In this study, we elucidated the protective effects of carveol in liver injury, using molecular and in silico approaches. Male BALB/c mice were divided into two experimental cohorts, to identify the best dose and to further assess the role of carveol in the nuclear factor E2-related factor; nuclear factor erythroid 2; p45-related fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Furthermore, studies have suggested increased COX-2 induction in the mouse brain after electrical kindling of hippocampal pyramidal cells [ 10 ]. Carveol significantly ameliorated the upregulated inflammatory mediators in PTZ-treated animals, which is consistent with recent findings regarding the modulatory effect of carveol on proinflammatory cytokines [ 33 , 59 ]. ATRA treatment further exacerbated the expression of inflammatory markers and abolished the anti-inflammatory potential of carveol, which supports our hypothesis that carveol exerts its anti-inflammatory potential by modulating the Nrf2 pathway.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, studies have suggested increased COX-2 induction in the mouse brain after electrical kindling of hippocampal pyramidal cells [ 10 ]. Carveol significantly ameliorated the upregulated inflammatory mediators in PTZ-treated animals, which is consistent with recent findings regarding the modulatory effect of carveol on proinflammatory cytokines [ 33 , 59 ]. ATRA treatment further exacerbated the expression of inflammatory markers and abolished the anti-inflammatory potential of carveol, which supports our hypothesis that carveol exerts its anti-inflammatory potential by modulating the Nrf2 pathway.…”
Section: Discussionsupporting
confidence: 92%
“…For this purpose, extensive research must be conducted on phytochemicals before human clinical trials as neuroprotectants [ 58 ]. Previous studies have shown that carveol is a monoterpene possesses robust antioxidant, anti-inflammatory, and protective properties in various degenerative models [ 33 , 59 ]. However, there have been no direct reports regarding the antiepileptic potential of carveol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GST activity was measured using CDNB as a substrate, as described previously with a slight modification. 41 Each well was filled with 10 μL of 1 mM CDNB, 10 μL of 5 mM reduced glutathione, 270 μL of buffer solution, and 10 μL of the sample. The absorbance was read at 340 nm using a plate reader.…”
Section: Glutathione-s-transferase (Gst) Activitymentioning
confidence: 99%
“…8 Carveol could be a powerful antioxidant and anti-inflammatory agent, activating the master endogenous protein Nrf2 which is an integral part of the cellular defense mechanism against oxidative stress and electrophilic aggression. Nrf2 joins the antioxidant response elements at the promoter site, which in turn encodes various phase II detoxifying and antioxidant enzymes and other important stress response factors, [80][81] and may be associated with negative modulation of p-JNK and other neuroinflammatory mediators. Therefore, it may offer a new therapeutic option to prevent and control oxidative stress and inflammation in degenerative disorders.…”
Section: Mechanisms Of Action Of Essential Oilsmentioning
confidence: 99%